89Zr-leukocyte labelling for cell trafficking: in vitro and preclinical investigations - Maryke Kahts; Hua Guo; Harikrishna Kommidi; Yanping Yang; Haluk Burcak Sayman; Beverley Summers; Richard Ting; Jan Rijn Zeevaart; Mike Sathekge; Omer Aras (SpringerOpen, 2023)
Abstract Background The non-invasive imaging of leukocyte trafficking to assess inflammatory areas and monitor immunotherapy is currently generating great interest. There is a need to develop more robust cell labelling and imaging approaches to track living cells. Positron emission tomography (PET), a highly sensitive molecular imaging technique, allows precise signals to be produced from radiolabelled moieties. Here, we developed a novel leukocyte labelling approach with the PET radioisotope zirconium-89 (89Zr, half-life of 78.4 h). Experiments were carried out using human leukocytes, freshly isolated from whole human blood. Results The 89Zr-leukocyte labelling efficiency ranged from 46 to 87% after 30-60 min. Radioactivity concentrations of labelled cells were up to 0.28 MBq/1 million cells. Systemically administered 89Zr-labelled leukocytes produced high-contrast murine PET images at 1 h-5 days post injection. Murine biodistribution data showed that cells primarily distributed to the lung, liver, and spleen at 1 h post injection, and are then gradually trafficked to liver and spleen over 5 days. Histological analysis demonstrated that exogenously 89Zr-labelled human leukocytes were present in the lung, liver, and spleen at 1 h post injection. However, intravenously injected free [89Zr]Zr4+ ion showed retention only in the bone with no radioactivity in the lung at 5 days post injection, which implied good stability of radiolabelled leukocytes in vivo. Conclusions Our study presents a stable and generic radiolabelling technique to track leukocytes with PET imaging and shows great potential for further applications in inflammatory cell and other types of cell trafficking studies.